Experiências de travestis e transexuais nos serviços de saúde na perspectiva da integralidade - Macêdo, Lizziane Aparecida Silva de (2020)
Introduction: The National Policy for Comprehensive Health for the LGBT population (PNSILGBT) is a watershed in the recognition of the health demands of the lesbian, gay, bissexual, transvestotes and transexual population, legitimizing health needs and their specificities. Transvestites and transexual identities represent individual and internal manisfestations. The relationship of these identities with health brings to the center of the discussion questions about health rights and their social visibility. Objective: to analyse the experiences of transvestites and transsexuals about their rights and meeting their demands in health services. Methodology: Descriptive study with a qualitative approach, conducted in a municipality in the northeast. Transvestites and transsexuals who used health services by the snowball technique were selected to conduct individual interviews. The data were analyzed using the contente analysis technique, in the thematic category. Results: the data showed advances and setbacks in the legal framework for the rights of the LGBT population in Brasil, in Paraíba and in the municipality of Campina Grande – PB; that the rights guaranteed by law are not enforced in the use of health services. As for the experience of using the social nome in health services, it was perceived as being both satisfactory and unsatisfactory depending on whether or not this use was respected; The principle of comprehensive care experienced by transvestites and transsexuals has not yet materialized in its full scope, but has advanced in terms of specific demand. Conclusion: the national policy for integral health of the LGBT population brought significant changes to the access of transvestites and transsexuals to SUS, but the study points out the need to democratize information about the transsexualization process. It also points out the low sensitivity of primary health care to the health needs of transvestites and transsexuals and the LGBT population in general, although it highlights its role as a gateway in the use of services.